Asuhan Keperawatan Keluarga Pada Pasien Dengan Rheumatoid Arthritis di Wilayah Kerja Puskesmas Batuhampar Tahun 2026 - Dara Atma Negara; Armaita Armaita; Vivi Yuderna; Kheniva Diah Anggita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Rheumatoid arthritis is a chronic disease of the musculoskeletal system that is a global health problem and if left untreated, rheumatoid arthritis can cause body parts to not function properly, such as the appearance of lumps, stiff joints, difficulty walking, and even lifelong disabilities. Globally, it is estimated that around 18 million people in the world suffer from rheumatoid arthritis, in Indonesia it reaches 23,711 cases, while in West Sumatra the prevalence is 7.21%. The purpose of this study is to be able to carry out family nursing care for rheumatoid arthritis patients including assessment, diagnosis, intervention, implementation, and evaluation. This study was conducted at the Batuhampar Community Health Center from February 23 to February 28, 2026 with 1 family of Mr. A using observation, interview, physical examination, education and documentation study methods. The results of the study found 3 nursing problems: knowledge deficit, ineffective health management, and health behaviors that tend to be risky. The nursing interventions provided were health education, decision-making support, family involvement and promotion of health-effort behavior. After 6 days of nursing implementation, knowledge increased, health management improved and health behaviors improved. It is hoped that patients can maintain their diet, adopt a healthy lifestyle, have regular check-ups at health facilities and do light physical activity.